Milk: Bioactive Components and Role in Human Nutrition - Alessandra Durazzo (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Milk is a nutritious food item with various beneficial properties and has a long tradition in nutrition, having been part of human diet for thousands of years. The composition of milk varies among different species, and milk quality is affected by several factors, i.e., season, climate, feeding management, and stage of lactation, as well as heat-treatments and technological processes. Milk is a valuable source of bioactive components and its role and function in human diet has been increasingly investigated by epidemiological and experimental studies. Consumption of milk is influenced by several variables, i.e., sex, age, ethnicity, and other cultural factors, and specific recommendations vary from country to country. This book includes original researches and review papers, and provides an overview of the nutritional composition and profile of the bioactive components of milk, its variation, and its impact on human diet.